Istikhdâm Tarîqah Tadrîs al-Aqrân fî Ta’lîm Mahârah al-Kalâm - Setiawan, Agung; Muna, Wa; Wicaksono, Meidias Abror (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2023)
Purpose- The research aims to know the implementation of the process of teaching speaking skill in a peer-teaching method in the Department of Arabic Language Education Sunan Kalijaga State Islamic University Yogyakarta and Kendari State Islamic University. Design/ Metodology/ Approach- This research is a descriptive qualitative research in which the respondents in this study were lecturers and students of speaking skills from UIN Sunan Kalijaga and IAIN Kendari. Data collection uses the method of observation and documentation. Data were analyzed with descriptive analytical method. Findings- The results of this study indicate that learning speaking skills using the peer-teaching method was considered effective for students because all students were actively involved in the learning process. Lecturers use the peer-teaching method due to obstacles in the form of differences in students' abilities to speak Arabic and educational background. The steps taken in learning speaking skills with the peer-teaching method consist of three stages. First, preparatory stage consists of: (1) identifying the student environment to determine strategies, (2) determining groups, (3) determining the role of each member in the group, (4) training peers as tutors, (5) preparing learning materials, (6) preparing assessments. Second, implementation stage consists of: (1) peers teaching group members, (2) peers using the role of teacher for error correction procedures. (3) students take turns performing in groups. Third, assessment stage consists of: (1) evaluation after learning activities and (2) final evaluation. Research Limitation/ Implications- The limitations of the problem in this research focus on learning speaking skills using the peer-teaching method and have not discussed other methods of learning speaking skills. However, this study describes the steps for learning speaking skills using the peer-teaching method from UIN Sunan Kalijaga and IAIN Kendari so that this good learning process can be implemented in other language skills.